Teaching Design and Practice of Chinese Film Course at Binus University - Ruomei, Fu (Humaniora, 2015)
The Chinese department of Binus University opened the course of Chinese film. This course aims to improve the students’ Chinese language skill, and at the same time, on the basis of Chinese proficiency, to improve their knowledge of Chinese history and cultural understanding of China, to cultivate their connoisseurship of Chinese film. Two versions of the course syllabus i.e. version 2008 and version 2013 wereintroduced in this article. Syllabus and teaching practice figured out the most suitable teaching content and teaching method for the course. Research found that the combination of classic movies and popular movies, the course of Chinese film, in conjunction with the literature course is the best way. By this method, the course of Chinese Film plays a better role in improving students' Chinese proficiency and virtuosity level.